(Not Finding a) Sequential Order Bias in Elite Level Gymnastics. (29th January 2015) - Rotthoff, Kurt W.
<x xml:space="preserve">Abstract</x> Sequential order bias is often used to refer to timing biases in sequential order judging. However, there are two distinct biases within this structure: overall order bias, a bias throughout the event, and a sequential order bias, a judgment biased by the immediately preceding performance. I independently test these forms of bias using uniquely suitable data from elite level gymnastics. After modeling overall order bias, I find evidence that this bias exists, as scores escalate throughout the competition. However, I find no evidence of a sequential order bias; scores are independent of the immediately preceding performer.